Keluarga Tangguh: Komunikasi Efektif Orang Tua dan Anak untuk Meningkatkan Pemahaman Mengenai Perkembangan Psikologis Anak di Desa Tanjung Lago - Safira Dwi Ramadhanti; Rina Oktaviana (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This Community Service Program (KKNT) was conducted in Tanjung Lago Village with a focus on strengthening families through effective communication between parents and children. The background of the program is the lack of parental understanding of children's psychological development, especially during adolescence, which may lead to rigid and less adaptive parenting styles. The aim of this activity is to provide psychoeducation on the stages of child psychological development based on Piaget’s and Hurlock’s theories, as well as to train effective communication skills such as active listening and the use of I-Messages. The method used was an educational workshop with a participatory approach, supplemented by self-reading modules for parents. The results showed a significant increase in parents' understanding of adolescent developmental characteristics, a shift from instructive to dialogic parenting patterns, and the creation of more harmonious two-way communication. Additionally, the distributed modules successfully served as independent literacy instruments that supported program sustainability. It can be concluded that family-based psychoeducational interventions are capable of strengthening family resilience and supporting children's psychological well-being amidst the challenges of the Industry 4.0 era.